The Impact of the Global Crisis on Canada-What Do Macro-Financial Linkages Tell Us? - Duttagupta, Rupa.; Barrera, N. (Washington, D.C. : International Monetary Fund, 2010)
This paper builds a Bayesian VAR estimation model of growth for Canada, by focusing specifically on the role of external and domestic financial indicators, including credit conditions. A variance decomposition shows that financial conditions explain one-third of the total variability in Canada's real GDP growth, although changes in U.S. real GDP growth still account for a larger share of volatility in Canadian growth. A macro-financial conditions index built from the VAR's impulse responses shows that U.S. real GDP growth and lending standards will increasingly bear on Canada's growth, implying that a normalization of the U.S. economic and financial conditions is key for a sustained recovery in Canada.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet